What the mathematics in the puzzles and handicrafts in 1920s Danish children's magazines tells us about childhoods. (December 2019) - Lange, Troels; Meaney, Tamsin
Media for children reflects societal views about appropriate childhoods in that the content has been chosen based on adults' views of what is appropriate for children to engage with. In this article, the mathematics in puzzles and handicrafts in a selection of Danish children's magazines from 1925 to 1930 are analysed to understand the childhoods that adults at this time considered appropriate. The classification of the puzzles and handicraft tasks according to the mathematical activities involved provides insights into the cultural practices deemed suitable for children and whether these cultural practices were differentiated according to gender. The analysis shows that there was a predominance of measuring and designing activities with children engaging in adult-equivalent tasks such as building a henhouse. These tasks had limited specific instructions, indicating that children needed to persevere in working out the details and have the resourcefulness to adapt them to their own situation. In addition, there are only a few features that aligned tasks to a particular gender. The puzzles and handicrafts indicate that appropriate childhoods were considered to be those that treated children as autonomous and valued the importance of doing things.